2019
DOI: 10.12998/wjcc.v7.i18.2888
|View full text |Cite
|
Sign up to set email alerts
|

Drug coated balloon angioplasty for renal artery stenosis due to Takayasu arteritis: Report of five cases

Abstract: BACKGROUNDTakayasu arteritis is a rare but intractable chronic disease in young female patients. Percutaneous transluminal angioplasty of the involved renal arteries has been reported; however, few studies have reported the use of drug coated balloon angioplasty in the treatment of Takayasu arteritis. We aimed to demonstrate five young female patients who presented with a history of hypertension due to Takayasu arteritis.CASE SUMMARYFrom April 2017 to October 2018, five female patients were diagnosed with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Notably, Yamamoto et al reported a case of a patient with aortitis-induced renal artery stenosis who underwent multiple renal angioplasty treatments before achieving blood flow velocities similar to those after two years of drug balloon therapy ( 94 ). Similar outcomes were observed in five patients with aortitis who received pharmacological balloon treatment, as reported in another study ( 66 ). Nevertheless, further research is required to fully understand the efficacy of drug balloon therapy for aortitis-related renal artery stenosis.…”
Section: The Application Of Drug Eluting Balloon In Arterial Circulat...supporting
confidence: 88%
“…Notably, Yamamoto et al reported a case of a patient with aortitis-induced renal artery stenosis who underwent multiple renal angioplasty treatments before achieving blood flow velocities similar to those after two years of drug balloon therapy ( 94 ). Similar outcomes were observed in five patients with aortitis who received pharmacological balloon treatment, as reported in another study ( 66 ). Nevertheless, further research is required to fully understand the efficacy of drug balloon therapy for aortitis-related renal artery stenosis.…”
Section: The Application Of Drug Eluting Balloon In Arterial Circulat...supporting
confidence: 88%
“…7 Drug-coated balloon angioplasty has recently been used to treat stenotic lesions caused by Takayasu arteritis. 4,8 To our knowledge, the use of DCBs to treat arterial stenosis involving all the major branches of the thoracic aorta due to Takayasu arteritis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…3 Balloon angioplasty has been reported to have better long-term patency compared with stent placement for treatment of renal artery stenosis caused by Takayasu arteritis. 3 Drug-coated balloon (DCB) angioplasty has also been used to treat renal artery stenosis caused by Takayasu arteritis, 4 but to the best of our knowledge, the efficacy of DCB for treatment of stenosed thoracic arteries caused by Takayasu arteritis remains anecdotal. We present a case of a 24-yearold female with narrowing or occlusions of the innominate, right common carotid, left common carotid, left vertebral, left internal carotid, and left subclavian arteries who underwent vascular intervention by DCB angioplasty and stent placement.…”
Section: Introductionmentioning
confidence: 99%
“…DCB was used only in one TA patient with restenosis, and no restenosis has occurred in the past 2 years. Bi et al 23 used DCB to effectively treat five TA-related RVH patients (≤ 18 years old); no restenosis occurred during follow-up (range: 5.1–23.8 months). Larger studies are required to provide more definitive evidence of the effectiveness of DCB in pediatric RVH.…”
Section: Discussionmentioning
confidence: 99%